Cancer cachexia induces morphological and inflammatory changes in the intestinal mucosa. Issue 5 (15th July 2019) - Costa, Raquel G.F.; Caro, Paula L.; de Matos‐Neto, Emídio M.; Lima, Joanna D.C.C.; Radloff, Katrin; Alves, Michele J.; Camargo, Rodolfo G.; Pessoa, Ana Flávia M.; Simoes, Estefania; Gama, Patrícia; Cara, Denise C.; da Silva, Aloísio S.F.; et al.
Abstract: Background: Cachexia is a multifactorial and multiorgan syndrome associated with cancer and other chronic diseases and characterized by severe involuntary body weight loss, disrupted metabolism, inflammation, anorexia, fatigue, and diminished quality of life. This syndrome affects around 50% of patients with colon cancer and is directly responsible for the death of at least 20% of all cancer patients. Systemic inflammation has been recently proposed to underline most of cachexia‐related symptoms. Nevertheless, the exact mechanisms leading to the initiation of systemic inflammation have not yet been unveiled, as patients bearing the same tumour and disease stage may or may not present cachexia. We hypothesize a role for gut barrier disruption, which may elicit persistent immune activation in the host. To address this hypothesis, we analysed the healthy colon tissue, adjacent to the tumour. Methods: Blood and rectosigmoid colon samples (20 cm distal to tumour margin) obtained during surgery, from cachectic (CC = 25) or weight stable (WSC = 20) colon cancer patients, who signed the informed consent form, were submitted to morphological (light microscopy), immunological (immunohistochemistry and flow cytometry), and molecular (quantification of inflammatory factors by Luminex® xMAP) analyses. Results: There was no statistical difference in gender and age between groups. The content of plasma interleukin 6 (IL‐6) and IL‐8 was augmented in cachectic patients relative to those with stable weight ( P = 0.047 and P = 0.009, respectively). The number of lymphocytic aggregates/field in the gut mucosa was higher in CC than in WSC ( P = 0.019), in addition to those of the lamina propria (LP) eosinophils ( P < 0.001) and fibroblasts ( P < 0.001). The area occupied by goblet cells in the colon mucosa was decreased in CC ( P = 0.016). The M1M2 macrophages percentage was increased in the colon of CC, in relation to WSC ( P = 0.042). Protein expression of IL‐7, IL‐13, and transforming growth factor beta 3 in the colon was significantly increased in CC, compared with WSC ( P = 0.02, P = 0.048, and P = 0.048, respectively), and a trend towards a higher content of granulocyte‐colony stimulating factor in CC was also observed ( P = 0.061). The results suggest an increased recruitment of immune cells to the colonic mucosa in CC, as compared with WSC, in a fashion that resembles repair response following injury, with higher tissue content of IL‐13 and transforming growth factor beta 3. Conclusions: The changes in the intestinal mucosa cellularity, along with modified cytokine expression in cachexia, indicate that gut barrier alterations are associated with the syndrome.